If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (33b + -4) + -8(4b + 4) = -5 Reorder the terms: (-4 + 33b) + -8(4b + 4) = -5 Remove parenthesis around (-4 + 33b) -4 + 33b + -8(4b + 4) = -5 Reorder the terms: -4 + 33b + -8(4 + 4b) = -5 -4 + 33b + (4 * -8 + 4b * -8) = -5 -4 + 33b + (-32 + -32b) = -5 Reorder the terms: -4 + -32 + 33b + -32b = -5 Combine like terms: -4 + -32 = -36 -36 + 33b + -32b = -5 Combine like terms: 33b + -32b = 1b -36 + 1b = -5 Solving -36 + 1b = -5 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 1b = -5 + 36 Combine like terms: -36 + 36 = 0 0 + 1b = -5 + 36 1b = -5 + 36 Combine like terms: -5 + 36 = 31 1b = 31 Divide each side by '1'. b = 31 Simplifying b = 31
| log7/1^1 | | y=6/7-2x | | 16x+12=8x+36 | | 7.13x+21.39=42.78 | | ln(x+3)-ln(x-4)=3 | | 4(x-2)=2(x-2) | | 21=9x+3 | | 33y=8(4y-6) | | 16n+4n+4n-5n-18n=11 | | g^2-32g+256=0 | | 5/4m=7/12 | | -2y+6(y-8)=-28 | | 9x-4=4x+5 | | 250=50+25h | | 6x^3-864x=0 | | A+17=104 | | 7t-t-2t-3t=1 | | 63(6x)-63(2x)=63 | | w*2=36-5 | | z^2+(7-7i)z+(2-26i)=0 | | 18r+r+r-14r-4r=-20 | | 3(-13+4y)+7y=29 | | 750=400+49g | | M-1/4=8/9 | | 13.2=-16x^2+24t+16.4 | | 28(6x)-28(2x)=28 | | x^2+y^2+2xy+1=0 | | 81=6-4x | | 3x^2+6x=42 | | 3x^4-30x^3+75x^2=0 | | -.02=-1.2 | | 4x+2x+3=10x+3 |